Islamic Da‘wah in the Malay Peninsula: Contributions of the Sayyids of Early Times - Ahmad Fauzi Abdul Hamid; Shaikh Abdullah Hassan Mydin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2021)
This article traces the stellar accomplishments of the Sayyids, as descendants of the Prophet Muhammad are known in the field of Islamic da‘wah. For the many Sayyids who excelled as torchbearers of Islam in the Malay world, propagating Islam was a lifetime vocation that passed without the stress that we find in the modern world. Their da‘wah efforts encompassed such diverse undertakings as employing business acumen in confronting the challenges of colonialism and Malay court culture, immersing themselves in native communities via intermarriages and adoption of local customs, and carving a niche for themselves in local and international politics as advisors and emissaries. At grassroots level, da‘wah for them was inseparable from daily chores and mundane affairs. That Western colonialism hardly made any impact in directly desacralizing the Malays is a tribute to the success of the Sayyids’ da‘wah efforts, which served as a buffer against the religious implications of colonial encroachment into autochthonous institutions and lifestyle. By looking at some examples of how the Sayyids interacted with local communities in selected regions of the Malay world, this article traces part of this glittering history of da‘wah in the easternmost parts of the Islamic commonwealth. Most importantly, the Malay world’s Islamization was distinguished by lack of violence and emphasis on educational progress more than anything else.